Effect of cooking and packaging conditions on quality of semi-dried green asparagus during cold storage. (March 2018) - Sergio, L.; Cantore, V.; Spremulli, L.; Pinto, L.; Baruzzi, F.; Di Venere, D.; Boari, F.
Abstract: Ready-to-eat asparagus ( Asparagus officinalis L.) is a tasty food with excellent nutraceutical properties. In order to realize a new ready-to-eat product, in this study asparagus's spears were cooked by blanching or microwave, and then dehydrated until they reached a weight loss of 25%, and packaged in air or in modified atmosphere (30% CO2  + 70% N2 ). Sensorial, physico-chemical, biochemical, and microbiological parameters were evaluated during a 30 days storage period at 4 °C. The microwave cooking proved to be the most effective method to preserve green colour, improving the overall acceptability of the product. Moreover, the storage in the absence of O2 and in the presence of high CO2 percentage was the most effective method to preserve phytochemical composition, total antioxidant capacity, and hygienic quality. In conclusion, asparagus spears cooked by microwave, semi-dried, packaged in modified atmosphere and stored at 4 °C for 30 days retained their quality and sensorial properties. Highlights: Postharvest performance of semi-dried green asparagus spears was evaluated. Sensorial, physical, biochemical and microbiological parameters were evaluated. Spears cooked by microwave showed a better sensory evaluation than blanched. Modified atmosphere (30% CO2 +70% N2 ) packaging preserves more than air. The product in modified atmosphere can be stored for about 30 days at 4 °C.